Effect of microcrystalline cellulose on biodegradability, tensile and morphological properties of montmorillonite reinforced polylactic acid nanocomposites - Arjmandi, Reza (Korean Fiber Society, 2015)
The objective of this study is to investigate the effects of incorporating microcrystalline cellulose (MCC) on montmorillonite (MMT) reinforced polylactic acid (PLA) nanocomposites prepared by solution casting method. The biodegradability, tensile and morphological properties of PLA hybrid composites were investigated using soil burial test, tensile testing machine, field emission scanning electron microscopy, transmission electron microscopy (TEM) and optical microscopy. In addition, Fourier transform infrared spectroscopy (FTIR) was used to observe the interactions between fillers and PLA in the hybrid composites. Various amounts of MCC were added to the optimum formulation which was 5 phr of MMT to produce PLA/MMT/MCC hybrid composites. The biodegradability of hybrid composites increased compared to nanocomposite with 5 phr MMT content and neat PLA. Interestingly, the ductility of PLA/MMT/MCC hybrid composites increased significantly with the addition of 1 phr MCC filler. FTIR analysis revealed some interactions between PLA and both fillers in the hybrid composites. X-ray diffraction and TEM analyses revealed that incorporation of MCC filler into optimum formulation of PLA/MMT nanocomposites slightly decreased the interlayer spacing of MMT in the PLA/MMT/ MCC hybrid composites.